An Analysis of Exploring Personal Reading Histories for Learners of FKIP University of Riau - Delfi, Syofia; Diah, Fangiana Safitri; Jismulatif, Jismulatif (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
EFL learners majoring in English experience different reading histories which areinterested to be explored. It can be conducted through one of classroom activities in Extensive Reading. This article is based on the literature review for a study âExploring Personal Reading Histories for Learners of FKIP University of Riauâ. This article aims to describe how Exploring Personal Reading Histories is appropriate for the learners of FKIP University of Riau. Critical analysis was conducted in order to gain the aim of this study. The result of analysis shows how Exploring Personal Reading Histories is appropriate for Learners of FKIP University of Riau in terms of the context of Indonesian EFL learners and the activities of extensive reading for reading competency. The result of this review is expected to be meaningful for the study designed.